Dual-task during gait between elderly with mild cognitive impairment and Alzheimer: systematic review - Vanessa Santa Rosa Bragatto; Larissa Pires de Andrade; Paulo Giusti Rossi; Juliana Hotta Ansai
Abstract Introduction: Studies report that mobility changes could be present in early stages of Alzheimer's disease (AD) or even in previous stages, such as mild cognitive impairment (MCI). The use of motor tests, involving dual task, could facilitate screening and differentiation between elderly with AD and MCI. Objective: to verify if gait tests associated with secondary tasks could differentiate elderly with AD and MCI. Methods: We conducted a systematic review in Pubmed, Web of Science, Medline and Scielo databases. Of the articles included, we collected information about year of the study, characteristics of the sample and the dual task test studied. Results: The databases were accessed during November 2014 and August 2015 and a total of 198 scientific papers was obtained. After reading first the summaries and then the full texts, five studies were inserted in the review. Elderly with AD presented a reduction of gait speed and stride length, using executive functions and countdown as secondary cognitive tasks. The type of MCI appears to influence the differentiation with AD. Conclusion: The review showed that some gait tests associated with a secondary task differentiate elderly with AD and MCI. It emphasizes the need of new studies involving this issue in order to obtain cut-off points and facilitate prevention, early diagnosis and observation of cognitive impairment's evolution in clinical practice of elderly.